Growth, yield, water relation and its use in tuberose (Polianthes tuberosa) as influenced by irrigation regime and nitrogen level - Halepyati, Ashok S; Sujatha, K; Prabhakar, M (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during winter season of 1991-92 and 1992-93 to find out the influence of different irrigation regimes and N feltilization on growth, flower yield water use of ’Single’ tuberose (Polianthes tuberosa L.) on a well-drained sandy-loam soil. Irrigation Â equal to replenishing 120% of pan evaporation (Epan) showed the maximum growth, flower yield (10.04 tonnes/ha), spike length (88.0 cm), rachis leligth (22.2 cm), flowers/spike (38.8) and actual evapo-transpiration (551.2 mm). The transpiration rate (40.3 g/cm2/sec) increased with an increase in frequency of irrigation. The leaf temperature (32.7 degree C) and stomatal diffusive resistance (1.05 sec/cm) decreased with an increase in Epan replenishment. The water-use efficiency was the highest (22.8 kg/ha-mm) with irrigation given to replenish 40% Epan. The maximum growth, flower yield (10.23 tonnes/ha) and water-use efficiency (22.7 kg/ha-mm) were recorded with 400 kg N/ha.